A Need for Training: Preparing Juvenile and Family Court Judges on Military‐Related Issues. (March 2014) - Marsh, Shawn C.; Gonzalez, Carlene
Abstract This brief report presents a study undertaken to better understand the training needs of judicial officers related to military issues. A snowball sample of judicial officers and court‐affiliated stakeholders were asked to identify the most critical training topics regarding military issues in juvenile and family court, as well as rate the importance of 13 potential training topics. The highest rated training topics for judicial officers (N = 129) were the (1) Welfare of spouses and children, (2) Protocols to consider when selecting kinship care for children of deployed parents, (3) Mental and physical health consequences of military service and deployment, (4) Reporting standards regarding Intimate Partner Violence or Family Violence, as well as implications for civil case investigation, and (5) Education support for children of deployed parents. Findings suggest a desire in the field for specific training on a multitude of issues related to serving/veteran men and women, spouses, and dependents. Recommendations for such trainings are discussed.